Imagens e sons da Coreia do Sul em espaços transnacionais - Luã Ferreira Leal (Ciências Sociais Unisinos)
The article focuses the relationship between state agencies, entertainment companies, and industrial conglomerates in promoting South Korea’s images as a country that combines modernity and tradition. Between the re-democratization in the late 1980s and the mandate of Park Geun-Hye, started in 2013 and finished in 2017, after the impeachment process, the country invested in positioning itself as adjusted to the conditions of globalization with projects that stimulated cultural production, tourism, and accomplishment of sports mega-events. The proposal is to analyze the construction of imagined landscapes about South Korea as a way of understanding the new geography of transnational spaces.